Fractionation of Rare Earth Elements in Greisen and Hydrothermal Veins Related to A-Type Magmatism - Mikael Tillberg; Olga M. Maskenskaya; Henrik Drake; Johan K. Hogmalm; Curt Broman; Anthony E. Fallick; Mats E. Åström (Geofluids)
This study focuses on concentrations and fractionation of rare earth elements (REE) in a variety of minerals and bulk materials of hydrothermal greisen and vein mineralization in Paleoproterozoic monzodiorite to granodiorite related to the intrusion of Mesoproterozoic alkali- and fluorine-rich granite. The greisen consists of coarse-grained quartz, muscovite, and fluorite, whereas the veins mainly contain quartz, calcite, epidote, chlorite, and fluorite in order of abundance. A temporal and thus genetic link between the granite and the greisen/veins is established via high spatial resolution in situ Rb-Sr dating, supported by several other isotopic signatures (δ34S, 87Sr/86Sr, δ18O, and δ13C). Fluid-inclusion microthermometry reveals that multiple pulses of moderately to highly saline aqueous to carbonic solutions caused greisenization and vein formation at temperatures above 200–250°C and up to 430°C at the early hydrothermal stage in the veins. Low calculated ∑REE concentration for bulk vein (15 ppm) compared to greisen (75 ppm), country rocks (173–224 ppm), and the intruding granite (320 ppm) points to overall low REE levels in the hydrothermal fluids emanating from the granite. This is explained by efficient REE retention in the granite via incorporation in accessory phosphates, zircon, and fluorite and unfavorable conditions for REE partitioning in fluids at the magmatic and early hydrothermal stages. A noteworthy feature is substantial heavy REE (HREE) enrichment of calcite in the vein system, in contrast to the relatively flat patterns of greisen calcite. The REE fractionation of the vein calcite is explained mainly by fractional crystallization, where the initially precipitated epidote in the veins preferentially incorporates most of the light REE (LREE) pool, leaving a residual fluid enriched in the HREE from which calcite precipitated. Fluorite occurs throughout the system and displays decreasing REE concentrations from granite towards greisen and veins and different fractionation patterns among all these three materials. Taken together, these features confirm efficient REE retention in the early stages of the system and minor control of the REE uptake by mineral-specific partitioning. REE-fractionation patterns and fluid-inclusion data suggest that chloride complexation dominated REE transport during greisenization, whereas carbonate complexation contributed to the HREE enrichment in vein calcite.